Análisis del oxido de grafeno usado como aditivo para el concreto - Hinestroza Murillo, Jorge Hernán; Urrego Londoño, Mateo (Universidad Antonio Nariño, 2021)
In the world of engineering there is a need in the search to constantly improve, not only construction methods but also the innovation of new materials that can optimize construction processes and results, taking into account that from an economic point of view they are more competitive. Eventually findings emerge that provide new avenues to explore, such as what happened in 2004 when the world met Andre Geim and Konstantin Novoselov with their discovery of Graphene.